Joyful Learning as a Worthwhile Instructional Activity for English Beginner Students in the Post Covid 19 Pandemic Era - Maming, Khadijah; Patahuddin; A, Nasrullah; Sianna; Arsyad, Nur Ainun (Universitas Cokroaminoto Palopo, 2023)
During the Covid-19 pandemic, there were many ways that schools used to keep learning going, and one of the learning approaches that are meaningful and fun in the child's world is joyful Learning. SDIT Al-Furqan located in Enrekang regency, South Sulawesi, Indonesia, also felt the impact of the Covid-19 pandemic. The most visible effect is that their enthusiasm for Learning has decreased because they have been